Behavioral finance for private banking : from the art of advice to the science of advice - Bachmann, Kremena; De Giorgi, Enrico G., 1975-; Hens, Thorsten (Wiley, 2018)
An essential framework for wealth management using behavioral finance Behavioral Finance for Private Banking provides a complete framework for wealth management tailored to the unique needs of each client. Merging behavioral finance with private banking, this framework helps you gain a greater understanding of your client's wants, needs, and perspectives to streamline the decision making process. Beginning with the theoretical foundations of investment decision making and behavioral biases, the discussion delves into cultural differences in global business and asset allocation over the life cycle of the investment to help you construct a wealth management strategy catered to each individual's needs. This new second edition has been updated to include coverage of fintech and neurofinance, an extension of behavioral finance that is beginning to gain traction in the private banking space. Working closely with clients entails deep interpersonal give and take. To be successful, private banking professionals must be as well-versed in behavioral psychology as they are in finance; this intersection is the heart of behavioral finance, and this book provides essential knowledge that can help you better serve your clients' needs.-Understand the internal dialogue at work when investment decisions are made -Overcome the most common behavioral biases-and watch for your own -Learn how fintech and neurofinance impact all aspects of private banking -Set up a structured wealth management process that places the client's needs front and center Private banking clients demand more than just financial expertise. They want an advisor who truly understands their needs, and can develop and execute the kind of strategy that will help them achieve their goals. Behavioral Finance for Private Banking provides a complete framework alongside insightful discussion to help you become the solution your clients seek.